Local Government Strategies In Infrastructure Development In The Mountainous Areas Of West Seram - Mayalina Letekay; Zainal Abidin Rengifurwarin; Hengky Virgo Richardo Pattimukay (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
Infrastructure development in the mountainous areas of Elpaputih District, West Seram Regency, faces complex challenges related to geography, institutional capacity, and limited resources. This study aims to analyze the strategies employed by the local government in planning, implementing, and supervising infrastructure development, and to identify the key factors influencing their effectiveness. The research adopts a qualitative approach using in-depth interviews, field observations, and a review of planning documents and regional development reports. The findings reveal that the local government's development strategy is combinative, integrating formal, document-based planning (top-down) with emergent strategies derived from community needs and on-site conditions (bottom-up). The capacity of local actors and the quality of cross-sectoral coordination are crucial determinants of implementation success. However, the supervision mechanisms still encounter obstacles, particularly in technical monitoring and reporting systems, especially in remote mountainous villages with limited accessibility. This study concludes that the effectiveness of infrastructure development in Elpaputih District is strongly influenced by the adaptability of local government strategies, the strength of inter-actor collaboration, and the enhancement of local capacity. The study recommends strengthening participatory planning, improving field supervision through technology-based monitoring, and establishing sustainable coordination mechanisms to ensure more responsive and resilient infrastructure development.